The Extent of Glaciation in the Pechora Sea, Eurasian Arctic, Based on Submarine Glacial Landforms - Sergey Nikiforov; Roman Ananiev; Martin Jakobsson; Evgeny Moroz; Sergey Sokolov; Nikolay Sorokhtin; Nikolay Dmitrevsky; Elena Sukhikh; Igor Chickiryov; Yulia Zarayskaya; Anatoly Razumovskiy; Igor Semiletov (Geosciences, 2023)
The Pechora Sea is optimally located for studying the coalescence of a glacial and periglacial continental shelf zone in the high Arctic. Here, we present data acquired during cruises of the RV Akademik Nikolaj Strakhov in 2018–2021, revealing the distribution of submarine glacial landforms in the central part of the Pechora shelf area. Based on moraines and the distribution of glacial lineations, the extent of the ice sheet during the Last Glacial Maximum (LGM) is proposed. The crests of the moraine ridges and the slopes of their sides express a variation in morphology, and the ridges combine into irregular complexes. The moraines are primarily composed of coarse cobble-sized material with an addition of coarse sand and other sedimentary fractions. The mapped glacial landforms clearly indicate that an ice sheet extended over the area, while the Pechora basin, at the same time, was comprised of lowland characterized by a cryogenic subaerial landscape. Based on the result from this study, the extent and ice-flow pattern of the Barents-Kara Ice Sheet during the LGM were determined.